(untitled) (KULT_online, 2023)
Terrorizing Images: Trauma and Ekphrasis in Contemporary Literature explores how images of trauma open new ways of understanding the phenomenon of ekphrasis, the verbal representation of images in literature. Instead of rooting ekphrasis in the conventional rivalry between the visual and the verbal, the volume offers fresh points of view of the practice of incorporating images of terror in literary texts. As a result, ekphrasis is provided with new subjects and functions — thus remaining true to its ever-changing nature.